2018
DOI: 10.3324/haematol.2018.189928
|View full text |Cite
|
Sign up to set email alerts
|

ASXL2 regulates hematopoiesis in mice and its deficiency promotes myeloid expansion

Abstract: Chromosomal translocation t(8;21)(q22;q22) which leads to the generation of oncogenic RUNX1-RUNX1T1 (AML1-ETO) fusion is observed in approximately 10% of acute myelogenous leukemia (AML). To identify somatic mutations that co-operate with t(8;21)-driven leukemia, we performed whole and targeted exome sequencing of an Asian cohort at diagnosis and relapse. We identified high frequency of truncating alterations in ASXL2 along with recurrent mutations of KIT, TET2, MGA, FLT3, and DHX15 in this subtype of AML. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Our previous study reported DHX15 R222G mutation in a Chinese family with AML and some sporadic AML patients 4 . The same mutation has been reported in AML patients by other groups 5‐10 . Our study found DHX15 is upregulated and associated with poor outcomes, which indicates the importance of DHX15 and DHX15 R222G in AML pathogenesis.…”
Section: Introductionsupporting
confidence: 84%
“…Our previous study reported DHX15 R222G mutation in a Chinese family with AML and some sporadic AML patients 4 . The same mutation has been reported in AML patients by other groups 5‐10 . Our study found DHX15 is upregulated and associated with poor outcomes, which indicates the importance of DHX15 and DHX15 R222G in AML pathogenesis.…”
Section: Introductionsupporting
confidence: 84%
“…After induction II, there was no significant difference in the average VAF for the 2 groups. We also examined the clearance of nonrandom AML-associated mutations [29][30][31]51 by treatment regimen and by using a criterion of VAF ,1%. 30 The VAFs of all genes selected were ,1% after the second induction course, irrespective of the treatment arm.…”
Section: Discussionmentioning
confidence: 99%
“…Asxl2 encodes a member of a family of epigenetic regulators involved in the assembly of transcription factors at specific genomic loci. A previous study indicated that Asxl2 was necessary for maintaining steady-state hematopoiesis ( 41 ). ASXL2 interacts with peroxisome proliferator-activated receptor (PPAR)γ and PPAR-activated receptor during adipogenesis ( 42 ).…”
Section: Discussionmentioning
confidence: 99%